2009
DOI: 10.1002/hec.1421
|View full text |Cite
|
Sign up to set email alerts
|

Absence of appropriate hospitalization cost control for patients with medical insurance: a comparative analysis study

Abstract: Require a better government's supervision system over medical insurance expenses such as reforming methods of payments, building up new cost compensation mechanism, and unifying and stabilizing prices for each category of medicines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Studies on OOP spending for inpatient treatment show that insurance encourages individuals to go to higher-level care, with an approximate 3% rise in higher-level visitsmeaning people go to a county-level health care center rather than a township-level health care center, which is more centralized in the government hierarchy-and stay longer, with a marginal increase of 1.37 days for Rural Resident Insurance enrollees (2), raising the overall cost of care for insured persons (55). These contrasting forces, the increased insurance coverage but more expensive care at higher-level health care centers and greater utilization such as longer stays, drive much of the variation in research study results, depending on if the study measures burden sharing or total OOP expenses (26,40,71), and highlight the need for both cost control mechanisms and careful economic evaluations of the impact of reforms.…”
Section: Impact Of Insurance On Patientsmentioning
confidence: 99%
“…Studies on OOP spending for inpatient treatment show that insurance encourages individuals to go to higher-level care, with an approximate 3% rise in higher-level visitsmeaning people go to a county-level health care center rather than a township-level health care center, which is more centralized in the government hierarchy-and stay longer, with a marginal increase of 1.37 days for Rural Resident Insurance enrollees (2), raising the overall cost of care for insured persons (55). These contrasting forces, the increased insurance coverage but more expensive care at higher-level health care centers and greater utilization such as longer stays, drive much of the variation in research study results, depending on if the study measures burden sharing or total OOP expenses (26,40,71), and highlight the need for both cost control mechanisms and careful economic evaluations of the impact of reforms.…”
Section: Impact Of Insurance On Patientsmentioning
confidence: 99%
“…Three recent studies shed light on (iii). Pan et al (2008) examine the effect of insurance on the hospital costs of 10 medium-size urban hospitals in Guangdong province, focusing on four conditions where there is a high degree of consensus over diagnosis and treatment. They found that spending on insured patients was around 10% higher than that on uninsured patients.…”
Section: Insurance and Its Impactsmentioning
confidence: 99%
“…Liu et al, 1996) were arguing for a subsidized voluntary community health insurance scheme to replace the largely defunct CMS. The designs of the programs proposed were quite modest compared with the NRCMS that emerged in 2003. directive came into effect in 2003, permitting BMI members to claim reimbursement for expenses incurred at community health centers (Pan et al, 2008). At the time, however, community health centers were notorious for their poor service, and hence in 2005 the government announced its intention to create a network of new centers to provide high-quality preventive, primary and home care and rehabilitative services (Yip and Hsiao, 2008).…”
Section: China's Health Reforms Since 2002mentioning
confidence: 99%
“…Given that inpatient reimbursement rates are between 42% and 65% of inpatient costs, hospitalization continues to place a major financial burden on families. Moreover, studies have documented higher charges for insured patients (Pan et al , ).…”
Section: Discussionmentioning
confidence: 99%